2007
DOI: 10.1136/vr.161.3.94
|View full text |Cite
|
Sign up to set email alerts
|

Bovine viral diarrhoea virus infection of alpacas (Vicugna pacos) in the uk

Abstract: Three alpacas (Vicugna pacos) aged two to 22 months with a history of illthrift and diarrhoea were examined postmortem, and tissues were collected for histology, including immunohistochemical labelling for pestivirus antigen, virus isolation and TaqMan reverse transcriptase-pcr assay. Blood samples from two clinical cases and the remaining herd members were tested for bovine viral diarrhoea virus (bvdv) antibody by serum neutralisation, antigen detection and pcr assay. The three affected alpacas were positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 8 publications
2
36
1
Order By: Relevance
“…4,9 Previous reports on 4 confirmed PI alpacas identified virus in various organs but did not mention reproductive tissues or salivary gland. 5,8,15 Unlike those cases, the cria in this report had disseminated BVDV infections that included parotid salivary gland, esophagus, C1-C3, testes, prostate, and kidneys. Identification of virus in these organs indicates potential routes for transmission through communicative and reproductive behaviors.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…4,9 Previous reports on 4 confirmed PI alpacas identified virus in various organs but did not mention reproductive tissues or salivary gland. 5,8,15 Unlike those cases, the cria in this report had disseminated BVDV infections that included parotid salivary gland, esophagus, C1-C3, testes, prostate, and kidneys. Identification of virus in these organs indicates potential routes for transmission through communicative and reproductive behaviors.…”
mentioning
confidence: 51%
“…Similar signs have also been reported in other PI alpacas. 5,8,15 The similarities between the disease in cattle and alpacas suggest that the viral pathogenesis could be comparable.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported serologic evidence of exposure to rotavirus (RV), bovine parainfluenza-3 virus (BPIV-3), bovine herpesvirus-1 (BHV-1), bovine viral diarrhea virus (BVDV), foot-and-mouth disease virus (FMDV), bluetongue virus (BTV), bovine enterovirus (BEV), bovine adenovirus (Badv III), influenza A virus (IAV), and equine herpesvirus-1 (EHV-1) in domestic South American camelids, most from animals without clinical presentation of disease (Fowler, 1998;Mattson, 1994;Saraiva, 2004;Cabello et al, 2006;Celedó n et al, 2006;Evermann, 2006;Parreñ o and Marcoppido, 2006). Viral antigens were detected in domestic came-lids in the presence of clinical signs of disease for BVDV, adenovirus, EHV-1, West Nile virus (Mattson and Baker, 1994;Mattson et al, 2006;Parreñ o and Marcoppido, 2006;Foster et al, 2007), and equine arteritis virus (EAV) (Weber et al, 2006). Studies carried out on wild South American camelids under captive conditions have reported 95% antibody (Ab) prevalence to RV in guanacos from the Argentinean Patagonia region and the first isolation and characterization of RV in guanaco juveniles with acute diarrhea (Parreñ o et al, 2001(Parreñ o et al, , 2004.…”
mentioning
confidence: 99%